2016
DOI: 10.1177/1474704916648784
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Cutting Restricts Sociosexuality Among the Igbo People of Southeast Nigeria

Abstract: Female genital cutting (FGC) involves partial or total removal of the external female genitalia and causes detrimental effects on woman's physical and psychological health. Estimates suggest that 130 million women and girls have experienced FGC worldwide. A frequently cited reason for performing this procedure is to restrict female sexuality. To test this idea, we examined women's willingness to engage in uncommitted sexual relations (sociosexuality) among the traditional Igbo community in Southeastern Nigeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Reasons for FGC vary across contexts and individuals, but are characterised by sociocultural factors [10]. FGC is believed to ensure virginity before marriage, promote sexual restraint, improve marriage prospects, enhance fertility and prepare a girl for her role as a wife and mother [3,[11][12][13][14][15][16][17][18][19][20][21]. It is perpetuated by religion [3,16], despite predating all major religions [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for FGC vary across contexts and individuals, but are characterised by sociocultural factors [10]. FGC is believed to ensure virginity before marriage, promote sexual restraint, improve marriage prospects, enhance fertility and prepare a girl for her role as a wife and mother [3,[11][12][13][14][15][16][17][18][19][20][21]. It is perpetuated by religion [3,16], despite predating all major religions [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the few studies examining extra-pair sex during marriage are mixed. One found a higher proportion of women with FGC reported extra-pair sex (Oyefara, 2014), another found no significant difference (Yount and Abraham, 2007), and another found that women with FGC had a significantly lower incidence of extra-pair sex although the sample size was small (Onyishi et al, 2016). In summary, the majority of these studies find that FGC status is not a clear predictor of reducing women's sexual activity.…”
Section: Prior Literaturementioning
confidence: 99%
“…The idea that FGC impedes women's sexuality is consistent with some local views of FGC (Adongo et al, 1998;Skaine, 2005), however Hartung was the first evolutionary scientist to suggest that FGC might provide a fitness benefit for men by reducing their wives' desire for extramarital sex, and thus enhancing men's paternity certainty (Hartung et al, 1976). Paternity concern is proposed as one of the key drivers behind the persistence of the practice leading to a preference for marriage to women with FGC, which in turn encourages families to have FGC performed on their daughters to enhance their marriageability (Van Rossem and Gage, 2009;Onyishi et al, 2016). Unlike individual anti-cuckoldry behaviours, it is proposed that FGC (and other similar harmful cultural practices which restrict women) may be enforced indirectly by men's marriage preferences (Boyden et al, 2012;Mackie, 1996;Shell-Duncan et al, 2011;Gruenbaum, 2005).…”
Section: The Paternity Certainty Theory Of Female Genital Cutting (Fgc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, when it is practiced, FGC is perceived as a marker of female purity, faithfulness, cleanliness, and sexual inaccessibility (Abdelshahid & Campbell, ; Van Rossem & Gage, ; Yount, ). Families cut their daughters to prevent promiscuity and premarital sex, and potential husbands select wives who are cut to ensure the paternity of offspring (Onyishi, Prokop, Okafor, & Pham, ; Ross, Strimling, Ericksen, Lindenfors, & Mulder, ). For example, in Bobo‐Dioulasso, Burkina Faso, one man explained in an interview that excised women are better at controlling themselves, and women who have not been cut “never stay at home.…”
Section: Fgcmentioning
confidence: 99%